ENHANCING THE STUDENTS’ ABILITY IN STORY RETELLING THROUGH MOVIES - Indrawati, Lenny Agustina (Universitas Negeri Semarang, 2013)
The research was based on an experimental design at Pre-School of Mondial School in the academic year of 2011/2012. The objectives of the research are to investigate (1) the effectiveness of movie as a medium of teaching, (2) the significant deference in using movie as a media of treatment and using discussion strategy as a media of treatment in improving the students’ mastery in story retelling, (3) the students’ socio-cultural background takes part in determining their achievement besides the effect of seeing movies as a means of improving their story retelling ability. The empirical data were obtained from Pre-Test and the Post-Test. The data were then measured and analyzed in form of statistical and descriptive analysis. The result of this study showed that the group used movies as medium in story retelling got better improvement in the average scores than those without movies. Moreover, it was also found that most of the high achievers, both in the experimental group and in the control group, came from social environment with the more capability to encourage the students to make use of movies for the benefit of their study, especially of retelling story.